THE DUALITY OF THE ABSURD: AN EXISTENTIAL ANALYSIS OF ALBERT CAMUS’S "THE STRANGER" AND FRANZ KAFKA’S "THE TRIAL" (International journal of artificial intelligence, 2026)
This article provides a comparative scholarly analysis of the existential crises depicted in Albert Camus’s The Stranger and Franz Kafka’s The Trial. Rather than viewing these works in isolation, the study interrogates the "Absurd" as a dual-faceted phenomenon: the bureaucratic nightmare of Kafka and the philosophical indifference of Camus. By juxtaposing Meursault and Josef K., the paper elucidates how "The Court" serves as a unified metaphysical metaphor for the human condition. The research explores how these texts dialogue with each other regarding freedom, guilt, and the modern individual's struggle against systemic irrationality.